Influence of Osmotic and Nutritional Stress on Physiology of Penicillium fellutanum in Removal of Phosphocholine and Modification of Phospho-1-O-[N-Peptidyl-(2-Aminoethanol)] Phosphodiesters of Peptidophosphogalactomannan Species - Park, Yong-Il (American Society for Microbiology, 2000)
Addition of 3 M NaCl to 72-h cultures of Penicillium fellutanum in 2 mM phosphate resulted in an increase in percentage of extracellular peptidophosphogalactomannan III (pP(x)GM(iii)) and a decrease in that of pP(x)GM(ii). The magnitude of (31)P nuclear magnetic resonance signals at 1.47 and 1.33 ppm of phospho-1-O-[N-peptidyl-(2-aminoethanol)] phosphodiesters pP(x)GM(ii) and pP(x)GM(iii) decreased compared with controls. The data suggest that serine, glycine, and threonine residues from the 3-kDa peptide and from galactofuranosyl-6-O-phospho-1′-O-[N-peptidyl-(2-aminoethanol)] residues were the precursors of the needed choline-derived osmolytes.